The 1st International Electronic Conference on Forests—Forests for a Better Future: Sustainability, Innovation, Inter 2020
DOI: 10.3390/iecf2020-07975
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Weathering Effect on Surface of Heat-Treated Wood of Ayous (Triplochiton scleroxylon K. Shum)

Abstract: The wood characteristics due to weather conditions change over time, particularly the color that reflects chemical changes. Natural ageing is usually a relatively slow process; therefore, artificial ageing plays an important role in assessing the performance by shortening the time compared to natural weathering conditions. The aim of this research is to evaluate the color and reflectance variation of wooden surfaces due to artificial weathering obtained through a solar box chamber simulating outdoor conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This does not disagree with the practical data known from works [5,12], the authors of which, by the way, also associate a decrease in the water absorption of wood with a change in the structural composition. But, unlike the results of studies reported in [6,21], the data obtained on the effect of thermal modification on the properties of wood, in particular, on water absorption, suggest the following:…”
Section: Discussion Of Results Of the Study Of Changes In The Propert...supporting
confidence: 73%
See 1 more Smart Citation
“…This does not disagree with the practical data known from works [5,12], the authors of which, by the way, also associate a decrease in the water absorption of wood with a change in the structural composition. But, unlike the results of studies reported in [6,21], the data obtained on the effect of thermal modification on the properties of wood, in particular, on water absorption, suggest the following:…”
Section: Discussion Of Results Of the Study Of Changes In The Propert...supporting
confidence: 73%
“…The purpose of study [5] is to assess the change in color and reflectivity of wooden surfaces due to artificial weathering. The tests were carried out using a solar box chamber that simulates external conditions and subsequent leaching with water.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The color change a*, which tends to be close to 0, is due to cell degradation on the wood surface [18]. While changes in the color parameter b* tend to be caused by changes in the temperature around the wood [19].…”
Section: Resultsmentioning
confidence: 99%
“…By observing the values of the chromatic coordinates and the total colour difference expressed by ∆E*, we can determine that, in the case of thermally untreated samples, the variations are higher in the uncoated samples than in the coated samples, and the spray application mode has the lowest colour variation. On the other hand, thermally treated samples exhibit a very different situation that reflects the variability in these samples [27]. The application of the polyurethane coating highly reduces the lightness of the samples (from about 39 to 20-23) and increase the values of a* and b*, especially in the case of spray application, as shown in Figure 3.…”
Section: Colour Datamentioning
confidence: 99%
“…Moreover, previous works showed that thermally treated samples exhibited great variations in colour and chemical properties because of artificial ageing [27]. For this reason, surface protection could also be necessary in the case of thermally treated Ayous wood, leading us to test the protective affect a new mono-component polyurethane coating, which we applied to both untreated and heat-treated samples.…”
Section: Introductionmentioning
confidence: 99%